Portable Sea-Lite uses seawater - Nor Salwana, Mohammad Idris (2022)
PEKAN, 9 May 2022 – The tradition of putting up lights or lamps when Ramadan begins to approach its final days has become a tradition of the Malay community in Malaysia.